Eleanor & Park - Rowell, Rainbow (London : Orion Paperback, 2012)
"Set over the course of one school year in 1986, this is the story of two star-crossed misfits--smart enough to know that first love almost never lasts, but brave and desperate enough to try"--
Keywords: Love -- Fiction; Dating -- Fiction; High schools -- Fiction; Schools -- Fiction; JUVENILE FICTION / Love & Romance; Omaha (Neb.) -- History -- 20th century -- Fiction